2021
DOI: 10.1186/s40104-021-00626-7
|View full text |Cite
|
Sign up to set email alerts
|

NORHA, a novel follicular atresia-related lncRNA, promotes porcine granulosa cell apoptosis via the miR-183-96-182 cluster and FoxO1 axis

Abstract: Background Follicular atresia has been shown to be strongly associated with a low follicle utilization rate and female infertility, which are regulated by many factors such as microRNAs (miRNAs), which constitute a class of noncoding RNAs (ncRNAs). However, little is known about long noncoding RNAs (lncRNAs), which constitute another ncRNA family that regulate follicular atresia. Results A total of 77 differentially expressed lncRNAs, including 67 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
39
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 23 publications
(40 citation statements)
references
References 66 publications
1
39
0
Order By: Relevance
“…We performed a subcellular localization assay by separating nuclear and cytoplasmic RNA and showed that miR-23a is more enriched in the nucleus than it is in the cytoplasm of pGCs ( Figure 2 A), indicating that miR-23a induces pGC apoptosis, possibly via an RNAa mechanism. Interestingly, an MRE motif was detected in the promoter region of the porcine NORHA , a pro-apoptotic lncRNA in pGCs ( Figure 2 B), when we previously analyzed its promoter sequence [ 19 ]. Furthermore, the two have a strong potential interaction ability with the -20 kcal/mol of the minimum free energy (MFE) ( Figure 2 C), so NORHA was selected for further investigation.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…We performed a subcellular localization assay by separating nuclear and cytoplasmic RNA and showed that miR-23a is more enriched in the nucleus than it is in the cytoplasm of pGCs ( Figure 2 A), indicating that miR-23a induces pGC apoptosis, possibly via an RNAa mechanism. Interestingly, an MRE motif was detected in the promoter region of the porcine NORHA , a pro-apoptotic lncRNA in pGCs ( Figure 2 B), when we previously analyzed its promoter sequence [ 19 ]. Furthermore, the two have a strong potential interaction ability with the -20 kcal/mol of the minimum free energy (MFE) ( Figure 2 C), so NORHA was selected for further investigation.…”
Section: Resultsmentioning
confidence: 99%
“…Our previous study demonstrated that FoxO1 , an effector for oxidative stress, is downstream of NORHA in pGCs [ 19 ]. Western blotting showed that the overexpression of miR-23a significantly induces the FoxO1 protein level in pGCs ( Figure 6 A).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations